(untitled) (VERITAS LEGIS JOURNAL, 2026)
The theoretical significance of the correct classification of misappropriation and embezzlement of entrusted property remains important for investigative and judicial practice in the Republic of Kazakhstan due to the fact that ambiguous understanding and interpretation of the provisions of criminal law with evaluative provisions is permitted, which entails a deviation from the uniform application of substantive law. The situation is further exacerbated by the emergence of new, complex methods for disposing of entrusted property, which characterize the objective and subjective aspects of this criminal offense in unconventional ways. Consequently, difficulties arise in classifying this act, especially when determining its relationship with civil and other legal relationships, leading to judicial errors. The author conducted a comprehensive and in-depth analysis of the current criminal law, regulatory decisions of the Supreme Court of the Republic of Kazakhstan, and monographic literature. He offers scientifically substantiated proposals for systematizing the conditions for recognizing property as entrusted to a person, the doctrinal interpretation of the unlawful seizure and appropriation of another’s property, and the moment of completion of this act.